6, 7-Dimethoxycoumarin Influences the Erythroid Differentiation of Human Chronic Myelogenous Leukemia K562 Cells through Regulating FOXO3/p27 Signal Pathway. (14th May 2022) - Zheng, Li; Wu, Yu; Wang, Fu; Shi, Hui; Xu, Bo; Yang, Aihua
Abstract : Objective . To study the pharmacological activity and the mechanism of action of natural compounds derived from 6, 7-dimethoxycoumarin on the differentiation of human chronic myeloid leukemia K562 cells. Methods . We use MTT assay (Sigma-Aldrich, USA) to detect cell viability; use flow cytometry to analyze DNA content for cell cycle analysis; use benzidine staining to synthesize hemoglobin to determine K562 cell differentiation; use western blot analysis and qPCR to detect the expression levels of FOX03, P27, CDK4, and their phosphorylation; and use the AOBS laser scanning confocal system (Leica, Wetzlar, Germany) to analyze and quantify the number of positive green spots. The statistical methods used are one-way analysis of variance (ANOVA) and Dunnett's test to analyze within and between groups. Results . In order to explore the effect of 6, 7-dimethoxycoumarin on the differentiation of K562 cell erythrocytes, it was concluded that 6, 7-dimethoxycoumarin promotes the differentiation of K562 cell erythrocytes; the proliferation of K562 cells was detected by MTT method, and the results showed that 6, 7-dimethoxycoumarin can inhibit the proliferation of K562 cells; to evaluate the effect of 6, 7-dimethoxycoumarin on the proliferation of K562 cells, the results showed that 6, 7-dimethoxycoumarin increased the expression of FOXO3, P27, CDK4, and CDK65, and decreased the phosphorylation of CDK4 and CDK6 proteins. To further explore the effect of knocking out FOXO3 on cell differentiation, the results show that 6, 7-dimethoxycoumarin can reduce the differentiation and proliferation of K562 cells by increasing the expression of FOXO3. Conclusion . This study extended the understanding of the pharmacological activity of 6, 7-dimethoxycoumarin and may provide a potential new target for the treatment of chronic myelogenous leukemia. However, we still need to further study the specific molecular capabilities of 6.7 dimethylcoumarin to understand their possible capture mechanism.